PRE-SERVICE TEACHER’S TEACHING COMPETENCE DURING KAMPUS MENGAJAR PROGRAM - Azizah, Nur; Maulina, Maulina; Nasrullah, Rahmat (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
Kampus mengajar is one of flagships of Merdeka Belajar Kampus Merdeka managed by indonesian ministry of education, culture, or higher education. The purpose of this study was to students’ perceptions of teaching competence about pre-service teachers during kampus mengajar program batch 6 by using quantitative descriptive design. A questionnaire with a Likert scale was used as a quantitative study to determine students' perceptions. Data collection was carried out by distributing questionnaire and observation to 62 students who took English class. The result of this study indicate that participants have a positive perception of Kampus Mengajar program to improve their competence as pre-service teachers. The perception of teaching competence was influenced by four aspects of pedagogic competence, personality competence, internet, communication, and technology competence, and Soft skill development. It reached 82% of pedagogic competence, 87% in personality competence, 99% in ICT, and 50% in soft skill development. Futhermore, the dominant aspect or indicator from the students’ perception of pre-service teachers in teaching competence is indicator 4. Kampus Mengajar program is highly recommended to be implemented in teachers by students and should be encouraged by each universities.